The Influence of Influencer Marketing, Electronic Word of Mouth (e-WOM), and Brand Awareness on the Decision to Play Roblox in Mataram City - Adinda Melisa Putri; Akhmad Saufi (LP2M IAIN Palopo, 2026)
The development of the online gaming industry in Indonesia prompted this study to analyze the influence of influencer marketing, electronic word of mouth (e-WOM), and brand awareness on the decision to play Roblox in Mataram City. The study aims to test the causal relationship between the three independent variables and the dependent variable using a causal associative quantitative approach. The population is the young generation of active Roblox players in Mataram, with a sample of 97 respondents selected purposively (aged 18-25 years). The instrument, a 5-point Likert questionnaire, was tested for validity (r > 0.196) and reliability (alpha > 0.60), analyzed using SPSS multiple linear regression after classical assumption testing. The results showed a significant simultaneous effect (R² = 0.693; F = 69.891, p < 0.05) and positive partial (influencer marketing β = 0.233 p = 0.012; e-WOM β = 0.480 p = 0.000; brand awareness β = 0.313 p = 0.000), with e-WOM being the most dominant. The conclusion states that all three factors effectively drive gaming decisions, different from physical product studies, with implications for regional digital marketing strategies